PROSES KOMUNIKASI VERBAL PEREMPUAN INDONESIA DI AUSTRALIA - Sri Seti Indriani; Ditha Prasanti (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2017)
Indonesian women that live in Australia have a different way in the verbal communication process than the citizens in Australia. They also are involved in many activities related to the culture tradition of Indonesia, like going to ‘asrisan’ or ‘pengajian’ group activities. Looking back on the background culture on where they live which is Australia, they tend to make new cultures. The research focused on how is the verbal communication process that applies within these Indonesian women in activity groups in Australia? The study uses a qualitative approach with a descriptive method. The data collecting technique used are depth interview, documentation study and observation. The result shows that the verbal communication that applies within the Indonesian women in activities group in Australia includes: (1) A new pattern of communication among the Indonesian women. (2) Topics discussed among them are Indonesia food; problems that occur in Indonesia and gossiping about other people. Keywords: Verbal Communication, Indonesian Women, Australia